Vozes Femininas: as mulheres publicistas nos jornais do norte brasileiro (1880 à 1892) - Bezerril, Fernanda Daniella de França (2013)
This work focuses on issues that have permeated public debates in the nineteenth century, involving issues related to the constitution of rights and struggle for citizenship and equality. The abolition of slavery and the prospect of a citizen inclusion referenced in the idea of the Republic inaugurated a new phase in the social construction of the country. Looking up, from the study of women's writings and directed for the women, check a process of social change in which it is proposed to build a new society, the more egalitarian in the tangent of gender relations. From the second half of the nineteenth century, even timidly, is already perceptible movement of claims of an expansion of the rights of political participation of women. This is amplified in the last decades of the Empire and beginning of the Republic. The period marks a rapid change in the direction of overcoming the patriarchal traditions in favor of an increasing participation of women in public debate political debate and ideological. This process was very clear and significant in the northern provinces of the country, as of Paraíba. The research aims reconstruct, from the study of political thought, based on primary sources, mainly involving collections of newspapers of epoch, the importance of the role of women in this time of great political and social transformations.